An evaluation of patient informed consent for dental extractions. Issue 3 (September 2022) - Arya, Richa; Jadun, Sarah; Shah, Aneesha
Dental practitioners are well versed in informing patients of the risks and benefits associated with dental extractions. The purpose of this service evaluation was to determine whether patients understood and recalled information relevant to their planned oral surgery procedure, prior to second stage consent. A questionnaire was distributed to patients who were attending for their elective treatment appointment. This explored their ability to recall the planned intervention, the modality of treatment (local anaesthetic, intravenous sedation, or general anaesthetic), understanding of alternative treatment options and the risks associated with the procedure. Completed responses were received from 29 of the distributed questionnaires (response rate=58%). The majority of patients were not aware of the following risks with their procedure: pain, bleeding, bruising, swelling, infection, damage to adjacent structures. Despite a well-documented consent form and comprehensive discussion, we identified that patients may not comprehend or recollect the risks associated with their dental extraction. As dental professionals we have a duty to seek ways to facilitate patient understanding and maximise their autonomy.